Examining How Immigration Waves Have Altered Cuban-American Politics - Browning, Jamie (My University, 2011)
Using recent survey data, this study found that common media portrayal of the Cuban-American population as homogeneously pro-Republican and anti-Castro is inaccurate. The data show clear differences between several cross-cutting groups, including those that live in Florida and those that do not. Also found were differences based upon whether the respondents came to the United States before or after the 1980 Mariel boatlift.
Color poster with text, photographs, and graphs.
Keywords: Immigrants--Political activity--United States--History; Cuban Americans--Politics and government; Posters